Acculturation, self-regulation, and depression among Turkish older immigrants: An SEM study - Bahar, Nazmiye Tugba; Degen, Nora Marie; Lang, Frieder (International Journal of Intercultural Relations, 2025)
This study explores the effect of acculturation attitudes and self-regulation strategies on depression among older Turkish immigrants in Germany. The study comprised 195 immigrants (105 women and 90 men) aged 75 + of Turkish origin, who participated in structured face-to-face interviews. A structural equation model (SEM) was conducted to examine the associations between latent variables and depressive symptoms. Flexibility in self-regulation played a protective role in depressive symptoms, while higher levels of orientation toward host culture was significantly related to depressive symptoms. Tenaciousness in self-regulation and orientation towards the culture of origin did not serve as significant predictors of depressive symptoms. However, a stronger orientation towards the host culture was associated with heightened self-regulation strategies. Further research should focus on the effect of self-regulation strategies on acculturation attitudes and depression.
CRIS-Team Scopus Importer:2025-08-08
Keywords: Acculturation attitudes; Depression; Old age; Self-regulation strategies; Turkish immigrants

IS THERE A WORRY ADVANTAGE? THE ROLE OF FEAR OF LONELINESS IN OLD AGE IN LONELINESS PREVENTIVE ACTIVITIES - Degen, Nora Marie; Kim-Knauß, Yaeji; Lang, Frieder (2023)

The Paradox of Aging-Related Fears: Fear of Loneliness in Old Age as a Motivator for Loneliness Preventive Activities - Kim-Knauß, Yaeji; Degen, Nora Marie; Lang, Frieder (Gerontology, 2024)
Introduction: Aging is often seen as a challenging process, prompting individuals to form emotional reactions in response to the perceived challenges associated with growing older, manifested as aging-related fears. The present study focuses on the fear of loneliness in old age, a significant concern considering the socioemotional importance of close relationships in later life. Drawing from proactive coping theory, the study explores the association between fear of loneliness and aging preparation. This research aimed to investigate whether the fear of loneliness motivates individuals to engage in activities aimed at preventing loneliness in old age. For exploratory purposes, we consider both linear and nonlinear effects at the interindividual level, as well as the intraindividual-level differences between fear levels and behavioral outcomes. In addition, we also investigate the moderating role of trait neuroticism in these associations. Methods: Data from the "Ageing as Future (AAF)"project in Germany (N = 1,183) spanning from 2012 to 2023 were utilized. A multilevel model considered both intra- and interindividual variations, incorporating timevarying variables and covariates. Results: Linear mixed model analysis revealed that increased fear of loneliness corresponded to heightened engagement in preventive activities linearly, while a quadratic term indicated an inverted U-shaped relationship. The inclusion of occasionspecific deviation scores showed that individuals were more inclined to engage in preventive activities when experiencing heightened fear of loneliness than usual. This impact of deviation in fear perception was particularly evident among those with high levels of trait neuroticism. Conclusion: The study reveals that fear of loneliness in old age is associated with proactive engagement in preventive activities, with those prone to higher levels of fear or worry being particularly affected. These results emphasize the importance of a moderate level of fear in driving action without succumbing to excessive pessimism or unrealistic optimism. The findings contribute to understanding the motivational role of aging-related fears and hold implications for gerontological practices, emphasizing the need for a balanced fear perception in addressing potential negative impacts of aging. Future research could explore moderators and long-term consequences of motivational aging-related fears.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Aging preparation; Aging-related fears; Loneliness; Preventive activities; Trait neuroticism